Taxonomy of calcareous sponges (Porifera, Calcarea) sampled on artificial substrates of a recreational marina in the Tropical Northeastern Brazilian coast - Chagas, Cléslei; Cavalcanti, Fernanda F. (Zootaxa, 2017)
Several specimens of calcareous sponges were sampled on artificial substrates of a recreational marina in Salvador, Bahia state, on the northeastern coast of Brazil. They belong to four species, two of which are new: Leucandra serrata, Paraleucilla incomposita, Sycon bellum sp. nov., and S. avus sp. nov. Leucandra serrata is recorded for the first time at the coast of Bahia, filling a large gap in the geographical distribution of this species, while the description of the specimens of P. incomposita revealed new characters that had previously been overlooked. Finally, the new species of Sycon described here differ from all the previously known species of the genus due to their skeletal organisation and spicule size. Our results increase the number of species known in Bahia from 13 to 17 and emphasise that areas with a large amount of artificial hard substrates can potentially harbour an interesting and unknown diversity of calcareous sponges.